The Effect of Company Operation Complexity, Audit Committee, and Audit Quality on Audit Report Lag with Board Gender Diversity as A Moderating Variable - Iqbal, Dzaky; Mintoyuwono, Danang (Jurnal Indonesia Sosial Sains, 2025)
This study was conducted to analyze the effect of the complexity of company operations, audit committees, and audit quality on audit report lag, with gender diversity in the board of directors as a moderating variable for coal mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The audit reporting lag is the time between the end of the fiscal year and the issuance of the audit report. The timely submission of audited financial accounts is critical because it influences the quality of financial information and stakeholders' economic decision-making. The sample for this study consisted of 26 coal mining sub-sector enterprises. STATA 17 was used for the study, with the Random Effect Model (REM) applied. Audit report lag was found to be unaffected by the complexity of corporate operations or audit committees, whereas audit quality had a negative impact. Meanwhile, gender diversity on the board has not been shown to mitigate the relationship between the complexity of corporate operations, audit committees, and audit quality, which affects audit delays. These findings provide significant contributions to corporate governance and our knowledge of the causes of audit report latency.